SEJARAH STATISTIKA: MANFAAT PEMBELAJARAN SEJARAH STATISTIKA DI ERA MODERN - Lia Listiati (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
The history of mathematics is a series of events related to the development of mathematics in the past. Statistics as one of the subjects in mathematics learning can also be presented through the history of statistics. Various studies state that the history of statistics can play a positive role in learning. In this case, it is necessary to discuss the benefits of learning the history of statistics in today's modern era. The purpose of writing this article is to find out the importance of applying the history of statistics in learning and to find out the steps of learning the history of statistics in the modern era. The design used is a mix method study and a qualitative study. The method used to write this article is literature study. The results of the literature study state that the application of the history of statistics in mathematics learning can motivate students to participate in mathematics learning. It can be seen from the activeness of students in learning activities. The history of statistics can also be a medium in the learning process that provides new experiences and makes learning mathematics more meaningful because it is connected with discoveries and everyday life. Therefore, the application of the history of statistics in mathematics learning is very necessary in today's modern era to support the mathematical abilities of students and teachers so as to create meaningful learning.